The Influence of Capital Adequacy Ratio and Financing to Deposit Ratio on Returns On Assets in Islamic Commercial Banks in Indonesia - Setiadi, Rezky Mehta; Hamidah, Nuh (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
This study analyzes the financial performance of Indonesian Islamic Commercial Banks by examining the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Return on Assets (ROA) on quarterly data for 2021–2022. This study investigates deviations from theoretical expectations regarding the relationship between CAR and FDR with ROA. Based on previous studies that reported inconsistent effects of these variables on profitability, this study explores the impact of CAR and FDR on ROA both individually and in combination. This study focuses on identifying the specific contribution of independent variables to ROA, both partially and simultaneously in the Islamic banking sector during the period. This study took a sample of nine banks registered on the official website of the Financial Services Authority (OJK), using a purposive sampling technique based on quarterly data resulting in 65 samples for observation. Multiple linear regression analysis through SPSS 25 shows that CAR has a positive and significant impact on ROA (t = 4.825 > 1.999, p = 0.000), as well as FDR (t = 2.119 > 1.999, p = 0.038). Together, CAR and FDR significantly affect ROA (F = 18.490 > 3.148, p = 0.000). Thus, this finding finds that there is a significant influence of CAR and FDR on ROA, both individually and together, so that it becomes important information in the framework of the financial performance of Islamic Commercial Banks in Indonesia.